Economic analysis of corporate governance failures in emerging markets - Dr. Vivek Saurav, Dr. Richa Kashyap, (European Economic Letters (EEL), 2025)
Corporate governance in the emerging markets is structurally, regulatory and behaviourally weak, eroding the efficiency of the firms and investor confidence. The article is an economic opportunity focused study on corporate governance failures in some of the emerging global economies including India, Brazil and South African markets. It also investigates how ownership structures, inefficiency by the boards, clash of agency as well as regulatory deficiencies aggravate governance risks. Using the examples of actual corporate corruption of Satyam (India), Petrobras (Brazil) and Steinhoff (South Africa), this research paper examines the economic implications of poor governance and suggests of reforms that will lead to more efficient market practices and protection of investors as well as corporate responsibility.